Lisinopril Protects Against the Adriamycin Nephropathy and Reverses the Renalase Reduction: Potential Role of Renalase in Adriamycin Nephropathy - Pengxun Han; Huili Sun; Yuanzhao Xu; Youjia Zeng; Wuyong Yi; Jia Wu; Mumin Shao; Shunmin Li; Tiegang Yi (Karger Publishers, 2013)
Aims: To investigate the potential role of renalase in adriamycin nephropathy and the effect of lisinopril on the regulation of renalase. Methods: Adriamycin nephropathy was induced in male Wistar rats (n=12) by a single injection of adriamycin at 2 mg/kg body weight. Rats were then randomly assigned to a model group or a treatment group, to which were administered distilled water or the angiotensin converting enzyme inhibitor lisinopril, respectively, for 12 weeks. Six normal rats served as controls. At the end of study, physiological parameters and systolic blood pressure were measured. Glomerulosclerosis and tubulointerstitial injury were assessed by histopathology Renalase protein expression in kidney was quantified by immunohistochemistry and immunoblotting. The serum concentration and urinary excretion of renalase were determined by enzyme-linked immunosorbent assay. Results: In model group rats, proteinuria and systolic blood pressure were elevated. Increased serum renalase concentration was observed; however, renalase protein expression in the kidney was significantly decreased. Compared with the model group, decreased proteinuria, lower systolic blood pressure, and fewer morphologic lesions were detected in the treatment group. Although levels of serum renalase were similar, accumulation of renalase in urine and kidney tissue increased notably in the treatment group compared with the model group. Conclusions: This study suggests that renalase may be involved in the process of adriamycin-induced renal injuries. Lisinopril may attenuate adriamycin-induced kidney injury by controlling blood pressure, which may be partially attributed to the renalase expression and secretion.